Kebijakan Hukum Pidana Terkait Dengan Penanganan Pengemis dan Gelandangan di Kota Lhokseumawe - Shira Thani; Fitria Mardhatillah; Muksalmina; Yuli Santri Isma; Fitri Maghfirah; Nabhani Yustisi; Tasyukur (Universitas Islam Tribakti Lirboyo Kediri, 2025)
A total of 50 beggars and homeless people have been recorded in Lhokseumawe City. This number has increased compared to the previous year, which recorded 37 beggars and homeless people. Article 34 paragraph (1) of the 1945 Constitution of the Republic of Indonesia affirms that the poor and neglected children shall be cared for by the state. In general, under Indonesia’s positive law, the activities of begging and vagrancy are classified as criminal acts. Substantively, criminal law provisions for beggars and homeless people remain necessary to address these issues in Lhokseumawe City. Based on this, the main problems are how criminal law policy regulates the handling of beggars and homeless people in Lhokseumawe City and how the implementation of criminal law enforcement is carried out against them. This research employs an empirical juridical method. The data sources consist of primary and secondary data, collected through interviews, observation, and document study, then analyzed qualitatively. The results show that there is no specific qanun (regional regulation) regarding beggars and homeless people. The existing criminal law policy still provides a legal basis for law enforcement against them. Efforts to address this issue include law enforcement, social rehabilitation, and social empowerment in accordance with Law Number 11 of 2009 and Government Regulation Number 31 of 1980. Therefore, handling beggars and homeless people can utilize provisions in the Indonesian Penal Code (KUHP), particularly Articles 504 and 505, which regulate begging and vagrancy in public places. The implementation of criminal law enforcement against beggars and homeless people in Lhokseumawe City still faces various obstacles in terms of legal structure, legal substance, and legal culture. Overall, law enforcement in this context requires regulatory reform, capacity building of law enforcement officers, and changes in the mindset of society and law enforcers to provide more effective and comprehensive solutions in addressing this issue.